Simulation of Free-Space Communication using the Orbital Angular Momentum of Radio Waves - Demeter, Áron; Kertész, Csaba Zoltán (IEEE, 2014)
The Orbital Angular Momentum (OAM) property of radio waves can be efficiently used to combine multiple free-space radio-communication channels into a single carrier frequency. This paper presents a study of such a multichannel system using Simulink model of radio-waves with different OAM value combined together. The study focuses on proving that OAM channels remain orthogonal at radio frequencies, and the OAM modulation of FSK, PSK and QAM modulated signals results in bit-error rates close to standard communication channel behavior in noisy environment.